Reading between the lines: exploring the unwritten rules of letters of recommendation in the Canadian resident selection process - Rachul, Christen; Collins, Benjamin; Porhownik, Nancy; Fleisher, William (Canadian Medical Education Journal, 2024)
Background: Efforts to better understand and improve letters of recommendation (LORs) in the resident selection process have identified unwritten rules and hidden practices that may limit their effectiveness. The objective of our study is to explore these unwritten rules and hidden practices more fully in one Canadian academic medical community. Methods: We conducted semi-structured, discourse-based interviews with 18 faculty members from the departments of Internal Medicine and Psychiatry at the University of Manitoba, Canada. Interviews were guided by sample LORs and were focused on experiences with either writing or reading LORs. We analyzed interviews using key concepts from genre theory and Aristotle’s appeals to ethos, logos, and pathos. Results: Participants described how the practices surrounding LORs are guided by unwritten rules. These practices contributed to writers’ use of visible strategies and textual silence to establish credibility, build a strong case, and appeal to readers. Readers rely on similar strategies, but not always as intended by the writers. Conclusions: The unwritten rules of one academic community can impede a nationally-facilitated resident selection process. Our findings highlight how critiques and potential improvements to LORs could benefit from considering the use of visible and invisible rhetorical strategies in specific contexts.